Twitter sebagai Medium yang Berpotensi Bagi Organisasi: Mengonstruksikan Pesan Hijau di Twitter - Tangguh Okta Wibowo; Khairul Syafuddin; Maria Advenita Gita Elmada (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2023)
This study examines the topic of environmental sustainability, which is currently emphasized by governments and organizations. How do organizations, in particular, utilize the term